Essential Atlas of technology (New delhi Sterling, 2006)
This information- packed atlas is a vividly illustated summary of human technology and its development from ancient tools and construction methods to today's bridges, highways, ships, planes,cars, electronic communications instruments, and even robots
Consistes of index
11 12
Keywords: Technology; The World Around Us(Inventions)